Action dual tasks reveal differential effects of visual imagery perspectives on motor performance. Issue 6 (June 2019) - Callow, Nichola; Edwards, Martin Gareth; Jones, Alex Lee; Hardy, Lew; Connell, Stephanie
Imagery research has identified two main visual perspectives, external visual imagery (EVI, third person) and internal visual imagery (IVI, first person). Based upon findings from brain imaging literature showing that different neural substrates are recruited for IVI and EVI perspectives, and that IVI activates motor system brain areas, we hypothesised that a concurrent action dual task would cause greater interference in performance for IVI than EVI. In a first experiment, participants were allocated to either an IVI or an EVI group, and were tasked with moving an onscreen marker towards a target in three blocked conditions: imagery, imagery with a concurrent motor dual-task of sequencing, and a math control. An interaction between imagery group and condition was driven by greater root mean square error for participants in the dual-task condition in the IVI group compared with the EVI group. We replicated the experiment with an eye-tracking objective measure of IVI; the results again showed that participants in the IVI group made more errors in motor movements, and an interference effect in eye movements, during the dual-task sequencing condition compared with the EVI group. The results of the two experiments reveal that a secondary motor task does interfere with IVI, providing behavioural evidence that IVI appears to rely on motor system processes more than EVI. These results have important implications for the use of visual imagery perspectives across a number of domains, with this paper being an essential reference for those conducting visual imagery perspectives research.